Review on CamGAP Adoption Barriers Adoption in Cambodia’s Vegetable Farmers - Sophea Phon; Mardy Serey; Tharath Lun (Journal of Academic Biology and Biology Education, 2026)
Purpose of the study: This review identifies technical, socioeconomic, and institutional barriers constraining Cambodian vegetable farmers from transitioning away from high‑chemical practices toward formal safety standards such as CamGAP. Methodology: Evidence was synthesized from peer‑reviewed studies, government manuals, and institutional reports published between 2010 and 2026. Main Findings: Results show that, although CamGAP adoption increases productivity, minimizes the amount of pesticide applied and results in increased economic returns under contract farming, the take up of CamGAP has been modest because of high certification and infrastructure costs; burdensome record‑keeping; weak consumer recognition; and market price parity with non‑certified produce. Institutional assistance from MAFF, PDAFF, NGOs and private sector has promoted training, subsidies and awareness, but caution among farmers is caused by market volatility and limited demand signals Novelty/Originality of this study: Taken together, CamGAP provides paths to modernization and safer production, but ongoing adoption will depend on stronger consumer awareness, consistent price premiums and continued institutional support to make certification viable for smallholders.